2003
DOI: 10.1007/s00442-002-1138-7
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography of sponge chemical ecology: comparisons of tropical and temperate defenses

Abstract: Examples from both marine and terrestrial systems have supported the hypothesis that predation is higher in tropical than in temperate habitats and that, as a consequence, tropical species have evolved more effective defenses to deter predators. Although this hypothesis was first proposed for marine sponges over 25 years ago, our study provides the first experimental test of latitudinal differences in the effectiveness of sponge chemical defenses. We collected 20 common sponge species belonging to 14 genera fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 128 publications
(87 citation statements)
references
References 80 publications
(115 reference statements)
2
81
1
1
Order By: Relevance
“…it has been shown that many of the bioactive compounds have an antipredatory function (e.g. Chanas and Pawlik, 1995;Pawlik et al, 1995;Becerro et al, 2003;Burns et al, 2003). occasionally, although rarely, an allelopathic function has been documented (Porter and Targett, 1988;Turon et al, 1996a;Thacker et al, 1998;engel and Pawlik, 2000).…”
Section: Scientia Marina 73(2)mentioning
confidence: 99%
“…it has been shown that many of the bioactive compounds have an antipredatory function (e.g. Chanas and Pawlik, 1995;Pawlik et al, 1995;Becerro et al, 2003;Burns et al, 2003). occasionally, although rarely, an allelopathic function has been documented (Porter and Targett, 1988;Turon et al, 1996a;Thacker et al, 1998;engel and Pawlik, 2000).…”
Section: Scientia Marina 73(2)mentioning
confidence: 99%
“…However, only a limited number of sponge samples have been screened. Also recently, a biological screening related the activities of sponge extracts from samples collected in tropical (Guam) and temperate (Indo-Pacifi c and Mediterranean) biogeographical areas, but of a limited number (20) of sponge species (Becerro et al, 2003). Therefore, it is of interest to screen a large number of sponge extracts, in order to verify the percent of active extracts and the relatedeness with the taxonomy of the sponges which yielded the most active crude extracts.…”
Section: Marine Spongesmentioning
confidence: 99%
“…Tropical and temperate sponges had comparable deterrence suggesting that chemical defenses from both tropical and temperate sponges were equally effective against predators. 231 In addition to predator defense, sponge extracts have been shown to display antifouling, antimicrobial, and allelopathic activities. For example, zooanemonin 43 and 3,4,5,6-tetrahydromethyl-3,6-dimethyl-4-pyrimidinecarboxylic acid 44 isolated from Protophlitaspongia aga collected in Palau have been reported to inhibit the settlement of cyprid larvae from Balanus amphiriteP 2 Recently, with the development of new marine microbiological techniques, the focus of sponge chemical ecology is moving toward antimicrobial activities of sponge extracts and metabolites.…”
Section: Spongesmentioning
confidence: 99%